Molecular Characterization of HEV Genotype 3 in Italy at Human/Animal Interface - De Sabato, Luca; Di Bartolo, Ilaria; Lapa, Daniele; Capobianchi, Maria Rosaria; Garbuglia, Anna Rosa (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) is an emerging public health issue in industrialized countries. In the last decade the number of autochthonous human infections has increased in Europe. Genotype 3 (HEV-3) is typically zoonotic, being foodborne the main route of transmission to humans, and is the most frequently detected in Europe in both humans and animals (mainly pigs and wild boars). In Italy, the first autochthonous human case was reported in 1999; since then, HEV-3 has been widely detected in both humans and animals. Despite the zoonotic characteristic of HEV-3 is well established, the correlation between animal and human strains has been poorly investigated in Italy. In the present study, we compared the subtype distribution of HEV-3 in humans and animals (swine and wild boar) in the period 2000-2018 from Italy. The dataset for this analysis included a total of 96 Italian ORF2 sequences (300 nt long), including both NCBI database-derived (n=64) and recent sequences (2016-2018, n= 32) obtained in this study. The results show that subtype 3f is the most frequent in humans and pigs, followed by the HEV-3e, HEV-3c and other unassignable HEV-3 strains. Diversely, in wild boar a wider group of HEV-3 subtypes have been detected, including HEV-3a, which has also been detected for the first time in a human patient in Central Italy in 2017, and a wide group of unassignable HEV-3 strains. The phylogenetic analysis including, besides Italian strains, also sequences from other countries retrieved from the NCBI database, indicated that human Italian sequences, in particular those of HEV-3f and HEV-3e, form significant clusters mainly with sequences of animal origin from the same country. Nevertheless, for HEV-3c, rarely detected in Italian pigs, human sequences from Italy are more correlated to human sequences from other European countries. Furthermore, clusters of near-identical human strains identified in a short time interval in Lazio Region (Central Italy) can be recognized in the phylogenetic tree, suggesting that multiple infections originating from a common source have occurred, and confirming the importance of sequencing support to HEV surveillance.